Publish, Don't Perish: Experienced Authors Share Ideas - Joyce E. Patterson; Evelyn A. Liss (Journal of Applied Communications, 1990)
In the past. many Extension agents and specialists didn't think much about "publish or perish." But with everchanging university administrators and policies, Extension workers now recognize the importance of publishing in refereed journals. Because of this, communication specialists are increasingly writing joumal articles and also are being asked to help subject-matter specialists and field agents prepare articles for publishing. Information gleaned from five Oregon State University faculty shows the importance of writing only about what interests you, getting to know others in your field, deciding where to market your work, seeking constructive criticism, and developing long-range strategies for publishing.